Prevention of Sexual Violence in Early Childhood Based on Parents’ Educational Level - Wahyu Purwasih; Ahmad Sahnan; Baiquni Rahmat (MUWAZAH : jurnal kajian gender, 2023)
Sexual violence in early childhood represents a multifaceted and urgent issue that demands systematic attention within educational and familial domains. This study aims to map the scholarly landscape concerning sex education, parental roles, and sexual violence, with a specific focus on how parental educational levels influence early childhood prevention efforts. Using a bibliometric analysis approach, data were extracted from 996 journal articles published between 2020 and 2022 through Publish or Perish software and subsequently analyzed using VOS Viewer. The analysis identified key thematic clusters, with parental education, school, and sex education emerging as the most frequently discussed topics. The results reveal a significant research gap in linking sex education with variables such as disability, child age, and socio-demographic factors. Furthermore, the findings underscore that sex education remains inadequately integrated into early childhood development, with many parents and educators perceiving the topic as taboo. This insufficient exposure contributes to children's vulnerability to sexual violence. The study highlights the necessity for more research exploring educators’ and parents’ roles in sex education, especially in relation to educational attainment. It calls for interdisciplinary collaboration to enhance sex education strategies and foster a culture of openness and protection for children.